High efficiency quantum dot light emitting diodes from positive aging. Issue 38 (19th September 2017) - Acharya, Krishna P.; Titov, Alexandre; Hyvonen, Jake; Wang, Chenggong; Tokarz, Jean; Holloway, Paul H.
Abstract : Colloidal quantum dot-polymer hybrid light emitting diodes (QLEDs) that exhibit external quantum efficiencies >12% for all three primary colors (21% from green) have been demonstrated. Abstract : Colloidal quantum dot-polymer hybrid light emitting diodes (QLEDs) that exhibit external quantum efficiencies >12% for all three primary colors (21% from green) have been demonstrated. These high efficiencies result in part from a positive aging effect reported here for the first time, where positive aging means the efficiency of the QLED increased with time. We have achieved 470 h operational life time ( T 90 ) at 2550 nits for red QLEDs. At longer times, negative aging phenomena lead to lower luminance and limit the lifetime of the QLEDs. It is concluded that we have reasonable control over the efficiency of QLEDs. The next challenge is to achieve lifetimes sufficiently long for all three primary colors for applications such as in television and illumination.